Clinical characteristics and outcomes of acute coronary syndrome patients with left anterior hemiblock. Issue 18 (19th May 2014) - Zhang, Hanfei; Goodman, Shaun G; Steg, Gabriel P; Budaj, Andrzej; Lopez-Sendon, Jose; Dorian, Paul; Huynh, Thao; Mangat, Iqwal; Wong, Graham C; Spencer, Frederick A; Yan, Andrew T
Abstract : Objective: We aimed to study the relationships between left anterior hemiblock (LAHB) and the patient characteristics, management, and clinical outcomes in the setting of acute coronary syndromes (ACS). Methods: Admission ECGs of patients enrolled in the Global Registry of Acute Coronary Events (GRACE) ECG substudy, and the Canadian ACS Registry I, were analysed independently at a blinded core laboratory. Multivariable logistic regression analysis was performed to assess the independent associations between LAHB on the admission ECG and in-hospital and 6-month mortality. Results: Of the 11 820 eligible ACS patients, 692 (5.9%) patients had LAHB. The presence of LAHB on admission was associated with older age, male sex, prior myocardial infarction, prior heart failure, worse Killip class, higher creatinine level, and higher GRACE risk score (all p<0.01). Patients with LAHB less frequently underwent cardiac catheterisation, coronary revascularisation or reperfusion therapy (all p<0.05). The LAHB group had higher in-hospital (6.9% vs 3.9%, p<0.001) and 6-month mortality (12.5% vs 7.7%, p<0.001). However, after adjusting for the known predictors of mortality in the GRACE risk models, LAHB was not independently associated with in-hospital death (OR 1.07, 95% CI 0.76 to 1.52, p=0.70), or death at 6 months (OR 1.00, 95% CI 0.75 to 1.34, p=0.99). Conclusions: Across the broad spectrum of ACS, LAHB was associated with significant comorbidities, high-risk clinical features on presentation, and worse unadjusted outcomes. However, LAHB was not an independent predictor of in-hospital and 6-month mortality and did not carry incremental prognostic value beyond the known prognosticators in the GRACE risk models.